Does More Spending on Education Matter to Human Capital Formation? Study Case of Bengkulu Province, Indonesia - Nurfitriani Nurfitriani; Romi Bhakti Hartarto (Magister Ilmu Administrasi Publik, 2018)
Based on Statistics Indonesia (BPS), Indonesia will face a demographic bonus era during 2020-2035. That implies that the number of productive-age population will be higher than elderly peopleand children (dependents). This phenomenon offers an opportunity due to a lower dependencyburden. However, the situation could be catastrophic if the government is not ready to equip theproductive age population with necessary skills. The objective of this study is to determine whetheror not higher spending on education has positive influence on human capital formation in BengkuluProvince. The research used panel data analysis of ten regions in Bengkulu Province for the 2010-2014 periods. Research results showed that spending on education does not have significant impacton human capital development, while women empowerment and infrastructure have positive effecton human capital. Our results imply that more spending on education does not matter if it is notsupported by quality infrastructure that makes education facilities accessible.